Korea’s Innovative Clusters and Development Strategies Focusing on the â€˜Loosely Coupledâ€™ Cooperation between the Daedeokinnopolis and the Pangyotechnovalley - Il Lee, Won; ., . (International Journal of Engineering and Technology, 2018)
In this paper, I review current status and development strategies in Korean innovation cluster. In particular, I compared the innovation clusters of Daejeon and Gyeonggi - do, and examined the differences and ways of cooperation. Among Daejeon and Gyeonggi-province innovation clusters, the DaedeokInnopolis is focused on R & D and pursues technology commercialization in connection with venture companies. Pangyo Techno Valley is a state-of-the-art IT technology centered on high technology companies. If wide-scale cooperation measures are established between Daejeon and Gyeonggi-do clusters, which are different from each other in the process of formation and complexity, a great synergy will be created at the national level. The future development strategy will be derived by examining the representative innovation cluster in Korea. The first strategic direction is to set up a vision of 'loosely coupled' between the Daejeon and Gyeonggi-do innovation clusters. The second strategic direction is to promote 'loosely coupled' wide-area cooperation programs between clusters. The third strategic direction is to foster an open innovation venture ecosystem.Â Â